Circulating miRNA in Patients Undergoing Total Pancreatectomy and Islet Autotransplantation. (23rd April 2021) - Vasu, Srividya; Yang, Jiemin M.; Hodges, James; Abu-El-Haija, Maisam A.; Adams, David B.; Balamurugan, Appakalai N.; Beilman, Greg J.; Chinnakotla, Srinath; Conwell, Darwin L.; Freeman, Martin L.; Gardner, Timothy B.; Hatipoglu, Betul; et al.
Circulating microRNAs (miRNAs) can be biomarkers for diagnosis and progression of several pathophysiological conditions. In a cohort undergoing total pancreatectomy with islet autotransplantation (TPIAT) from the multicenter Prospective Observational Study of TPIAT (POST), we investigated associations between a panel of circulating miRNAs (hsa-miR-375, hsa-miR-29b-3p, hsa-miR-148a-3p, hsa-miR-216a-5p, hsa-miR-320d, hsa-miR-200c, hsa-miR-125b, hsa-miR-7-5p, hsa-miR-221-3p, hsa-miR-122-5p) and patient, disease and islet-isolation characteristics. Plasma samples ( n = 139) were collected before TPIAT and miRNA levels were measured by RTPCR. Disease duration, prior surgery, and pre-surgical diabetes were not associated with circulating miRNAs. Levels of hsa-miR-29b-3p ( P = 0.03), hsa-miR-148a-3p ( P = 0.04) and hsa-miR-221-3p ( P = 0.01) were lower in those with genetic risk factors. Levels of hsa-miR-148a-3p ( P = 0.04) and hsa-miR-7-5p ( P = 0.04) were elevated in toxic/metabolic disease. Participants with exocrine insufficiency had lower hsa-miR-29b-3p, hsa-miR-148a-3p, hsa-miR-320d, hsa-miR-221-3p ( P < 0.01) and hsa-miR-375, hsa-miR-200c-3p, and hsa-miR-125b-5p ( P < 0.05). Four miRNAs were associated with fasting C-peptide before TPIAT (hsa-miR-29b-3p, r = 0.18; hsa-miR-148a-3p, r = 0.21; hsa-miR-320d, r = 0.19; and hsa-miR-221-3p, r = 0.21; all P < 0.05), while hsa-miR-29b-3p was inversely associated with post-isolation islet equivalents/kg and islet number/kg ( r = −0.20, P = 0.02). Also, hsa-miR-200c ( r = 0.18, P = 0.03) and hsa-miR-221-3p ( r = 0.19, P = 0.03) were associated with islet graft tissue volume. Further investigation is needed to determine the predictive potential of these miRNAs for assessing islet autotransplant outcomes.